2019
DOI: 10.9734/cjast/2019/v33i330079
|View full text |Cite
|
Sign up to set email alerts
|

Study on Different Methods of Weed Management in Onion (Allium cepa L.)

Abstract: A weed management study on onion (Allium cepa L.) was conducted at Birsa Agricultural University, Jharkhand, India during winter season of 2016-17 and 2017-18 in a randomized block design comprised of nine weed control treatments consisting plastic mulch, available weeds mulch, straw mulch, cover crops (Fenugreek), oxyfluorfen 0.5 kg/ha pre-emergent (PE), pendimethalin 1.0 kg/ha PE, mechanical weeding by Dutch hoe, hand weeding at 20, 40, 60 days after transplanting (DAT) and weedy check. Hand weeding at 20, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…These species are different in form, taste and colour [ 19 ], and have largely been consumed as spices, vegetables, and medicines since pre-historic times [ 5 ]. Allium cepa L. (onion/Piyaz), is one of the most important, and health beneficial vegetable crop cultivated on a large scale throughout the world (in >175 countries), mainly in Asia [ 20 ], and is ranked second after tomato [ 21 ]. Onion is a biennial herb belonging to the family Amaryllidaceae/Alliaceae, with bulbous, scented bulbs having various shapes and skin colour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These species are different in form, taste and colour [ 19 ], and have largely been consumed as spices, vegetables, and medicines since pre-historic times [ 5 ]. Allium cepa L. (onion/Piyaz), is one of the most important, and health beneficial vegetable crop cultivated on a large scale throughout the world (in >175 countries), mainly in Asia [ 20 ], and is ranked second after tomato [ 21 ]. Onion is a biennial herb belonging to the family Amaryllidaceae/Alliaceae, with bulbous, scented bulbs having various shapes and skin colour.…”
Section: Introductionmentioning
confidence: 99%
“…Onion is a biennial herb belonging to the family Amaryllidaceae/Alliaceae, with bulbous, scented bulbs having various shapes and skin colour. In 2020, estimated global production of onion was around 400,000 tonnes [ 20 ], which was 25% more than the past decade [ 22 ]. China is the leading country in term of area of onion cultivation and its annual production, followed by India, USA, Iran, Egypt, Turkey, and Russia, while Pakistan ranked 8 th in the world with 1939.6 thousand tonnes of production [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zangoueinejad et al, 2018, found that the highest yield per unit area was obtained from a plastic mulch (20.93 kg m-2), while the lowest (1.24 kg m-2) was observed in the control plots without plastic mulch. In onions, yield increased by up to 300% using plastic mulch (Barla and Upasani, 2019). Our results show that the combination of steaming and plastic mulching severely impaired weed competition and increased tomato yield by 136 and 158% at 5 and 20 min, respectively, than 0 min of steaming.…”
Section: Discussionmentioning
confidence: 70%
“…Pollination studies in Onion (Allium cepa L.) during 2017-18 was estimated to be 22.42 million tons from 1.28 million hectare area (Barla & Upasani, 2019;Mahmadajaruddin & Mamani, 2020). Although the supply of onions for various culinary purposes is met with sufficient quantities, the demand for seeds is always high and both the public and private sectors seldom meet the increasing demands (Panacci et al, 2020;Meghana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%